2004
DOI: 10.4319/lo.2004.49.4_part_2.1317
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton life cycles: Direct documentation of pelagic births and deaths relative to diapausing egg production

Abstract: Zooplankton demographics operate over multiple time scales corresponding to pelagic parthenogenetic generations, an overwintering stage, and an ''egg bank.'' Comparisons of pelagic birth and death rates with seasonal diapausing egg production provide insights into local species persistence. The spiny cladoceran (Bythotrephes) possesses morphological adaptations (spines and thick-walled diapausing eggs) that lessen, but do not eliminate, predation effects by fish. Because caudal spines are retained throughout l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 52 publications
1
53
0
Order By: Relevance
“…A combination of low prey availability and ineffective Bythotrephes predation due to poor light penetration through the water column in August and/or September could result in concurrent declines in Bythotrephes body length and population size. As seen in other lakes, however, predation by planktivorous fish at this time (Coulas et al 1998, Pothoven et al 2001, Jarnagin et al 2004, Pothoven and Vanderploeg 2004, Young and Yan 2008, Young et al 2009) may also be contributing to the midseason change in Bythotrephes body size in Lake Simcoe. The concurrent recovery of body and population size in the fall months in some years may be related to the recovery of cladoceran prey abundance and/or reduced or relaxed fish predation pressure (Pothoven et al 2001).…”
Section: Bythotrephes Life-history Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…A combination of low prey availability and ineffective Bythotrephes predation due to poor light penetration through the water column in August and/or September could result in concurrent declines in Bythotrephes body length and population size. As seen in other lakes, however, predation by planktivorous fish at this time (Coulas et al 1998, Pothoven et al 2001, Jarnagin et al 2004, Pothoven and Vanderploeg 2004, Young and Yan 2008, Young et al 2009) may also be contributing to the midseason change in Bythotrephes body size in Lake Simcoe. The concurrent recovery of body and population size in the fall months in some years may be related to the recovery of cladoceran prey abundance and/or reduced or relaxed fish predation pressure (Pothoven et al 2001).…”
Section: Bythotrephes Life-history Characteristicsmentioning
confidence: 99%
“…Bythotrephes typically recruits from diapausing (resting) eggs in May (Yurista 1992, Jarnagin et al 2004, Young 2008), yet Bythotrephes was not observed in pelagic samples in Lake Simcoe until June or July. The apparent absence of Bythotrephes in May and June may be related to low spring prey abundance because cladoceran abundance routinely did not begin increasing in the lake until June.…”
Section: Bythotrephes Seasonal Phenologymentioning
confidence: 99%
See 3 more Smart Citations